MODELING OF THE 10-YEAR SURVIVAL OF MEN 60 YEARS AND OLDER, WITH ISCHEMIC HEART DISEASE - I. V. Tancyreva; E. G. Volkova; S. Yu. Levashov; Yu. Yu. Shamurova (Кардиоваскулярная терапия и профилактика)
Aim. To invent 10-year survival model of the men >60 y.o. with ischemic heart disease (IHD), including prognostic significance of the traditional risk factors, electric remodeling parameters of myocardium and other factors comorbid with the fatal events and survival depending on the age.Material and methods. Study cohort consisted of 167 men with IHD at the age >60 y.o. (mean age 76,3±0,5). All persons in the cohort underwent complex clinical and functional assessment of cardiovascular system, the parameters of electrical activity of myocardium studied — value of the ventricles activation velocity, repolarization heterogeneity, and stages of electrical remodeling severity. All participants were followed-up during 10 years with the analysis of the disease course and fatal events monitoring. Survival analysis was done on the base of tables of lifetimes completion with the part of died, survived, of cumulative part of survived (survival function), density of the death probability, function of momentary risk.Results. In the cohort of men >60 y.o. with IHD cardiovascular death, mortality coefficients from all cases and from cardiovascular diseases, cumulative part of the survived, density of the probability of heath and the function of momentary risk in different age groups (I group 60-74 years and II group >75 years) сdid not differ significantly. Physical activity and high density cholesterol level >0,6 mmol/L are associated with the increase of survival rate in the 1st age group, as in the 2nd. Presence of arterial hypertension in IHD cohort of men was a predictor of fatal outcomes and increased mortality — odds ratio (OR) 2,469 (p<0,04). In the 2nd age group the main factor increasing mortality was the functional class of the heart failure — OR 3,672 (p<0,009). Electrical remodeling of myocardium in men older than 60 y. with IHD does not significantly associate with prognosis. As the predictors of fatal outcomes among the persons of the 1st age group were the velocity of ventricles activation (VVA) <39 s-1, OR 2,266 (р<0,044), for the persons of the 2nd age group — value of heterogeneity of VVA — OR 13,632 (p<0,04). Conclusion. 10-year prospective follow-up of the men cohort >60 y.o. with IHD made it possible to create a model of survival, which makes it to predict fatal events, to establish significant for prognosis factors and focus on the specific factors of fatal outcomes for various age groups inside this age cohort.